Self-regulation assessment among preschoolers with externalizing behavior problems - Graziano, Paulo A; Slavec, Janine; Ros, Rosmary; Garb, Leanna; Hart, Katie; Garcia, Alexis (Psychological assessment, 2015)
This study examined the construct validity and clinical utility of a brief self-regulation assessment (Head-Toes-Knees-Shoulders, HTKS) among a clinical sample of children with externalizing behavior problems (EBP). Participants for this study included 101 preschool children (72% male; Mage = 5.10 years; 79% Hispanic) with at-risk or clinically elevated levels of EBP. Self-regulation measures included the HTKS task, 4 standardized subtests from the Automated Working Memory Assessment (AWMA), parent and teacher reports of children's executive functioning (EF), and children's self-regulation performance across a series of executive functioning classroom games conducted as part of a summer treatment camp. Additional outcomes included school readiness as measured by standardized achievement tests, and parent and teacher reports of kindergarten readiness and behavioral impairment related to academic functioning. Performance on the HTKS task was moderately correlated with children's performance on the standardized working memory tasks and observed self-regulation performance in the classroom. Low to moderate correlations were observed between performance on the HTKS task and parent report of children's EF difficulties, as well as parent and teacher reports of children's kindergarten readiness and behavioral impairment related to academic functioning. Moderate to high correlations were observed between performance on the HTKS task and standardized academic outcomes. These findings highlight the promise of the HTKS task as a brief, ecologically valid, and integrative EF task tapping into both behavioral and cognitive aspects of self-regulation that are important for children with EBP's success in school.